Etika Kato Nan Ampek dalam Budaya Minangkabau: Studi Lokusi, Ilokusi dan Perlokusi - Yanti, Silvia Rahma; Amelia, Ulfi; Agustia, Dwi Putri; Susanto, Djoko (Jurnal Bahasa, Sastra, dan Budaya, 2024)
The Kato nan ampek is a polite language procedure that regulates Minangkabau society in socializing. Minangkabau customs originate from Islamic teachings, which are described in the terms "Adat Basandi Syarak", "Syarak Basandi Kitabullah", with the essence that Minangkabau customs cannot be separated from the influence of Islamic teachings. This research aims to describe the locutionary, illocutionary and perlocutionary speech acts in Kato Nan Ampek and the values contained in Kato Nan Ampek. This research uses qualitative methods with a literature study approach (library research) and preliminary research. The research results show that the use of locutionary, illocutionary and perlocutionary speech acts contained in Kato Nan Ampek is very important for understanding the culture and values of Minangkabau society. By observing these rules, society can minimize social disparities and strengthen relationships between individuals.Keywords: Ethics; Kato Nan Ampek; Values of Manners